Haplotypes of TNFα/β Genes Associated with Sex-Specific Paranoid Schizophrenic Risk in Tunisian Population - Inoubli, Oumaima; Jemli, Achraf; Ben Fredj, Sihem; Mechri, Anouar; Gaha, Lotfi; Bel Hadj Jrad, Besma (Disease Markers, 2018)
Several medical research findings have announced a strong association between the biology of cytokines and various brain activities. Since growing evidences suggest the crucial and complex role of the tumor necrosis factor in the CNS, we have hypothesized that functional genetic variants of the LTA and TNFA genes (LTA +252A/G (rs909253) and TNFA −857C/T (rs1799724) and TNFA −238G/A (rs361525)) may be involved in the predisposition to schizophrenia. This research is based on a case-control study. The RFLP-PCR genotyping was conducted on a Tunisian population composed of 208 patients and 208 controls. We found a strong significant overrepresentation of the minor alleles (G, T, and A, respectively) in all patients compared with controls (p=0.003, OR=1.55; p=0.005, OR=1.78; and p=0.0001, OR=1.74, respectively). This correlation was confirmed for male but not for female patients. Interestingly, the frequencies of the minor alleles were significantly more common among patients with paranoid schizophrenia when compared with controls (p=0.003, OR=1.75; p=5·10−6, OR=3.04; and p=4·10−6, OR=2.35, respectively). This potential association was confirmed by a logistic binary regression analysis only for the development of the paranoid form of schizophrenia (p=0.001/OR=2.6; p=0.0002/OR=3.2; and p=0.0004/OR=3.1, respectively) and remained not significant for the other subtypes. Moreover, our study showed an important association between GCA haplotype and the development of this pathological form (p=10−4, OR=3.71). In conclusion, our results proved a significant association between the three polymorphisms and paranoid schizophrenia, at least in the Tunisian population, suggesting a substantially increased risk for paranoid schizophrenia with dominant inheritance of these three minor alleles.